2013
DOI: 10.1016/j.paid.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in positivity offset and negativity bias: Gender-specific associations with two serotonin receptor genes

Abstract: Individual differences in the evaluation of affective stimuli, such as the positivity offset and negativity bias may have a biological basis. We tested whether two SNPs (HTR2A; 102T>C and HTR1A; 1019C>G) related to serotonin receptor function, a biological pathway associated with affective regulation, were differentially related to positivity offset and negativity bias for males and females. Participants were 109 cigarette smokers who rated a series of affective stimuli to assess reactions to positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It must be acknowledged here that, according to some authors [ 44 , 63 , 64 ], self-ratings of dream emotions based on emotion rating scales may be biased by demand characteristics of the rating task (i.e., individuals may be primed by answer options) or phenomena such as the positivity offset (i.e., the tendency to experience mildly positive mood most of the time [ 65 ]); still, several authors argue that self-ratings more validly represent dream emotional experiences [ 39 , 66 , 67 ]; see also [ 44 ] for an extensive discussion of pros and cons of self- and external dream emotion ratings). In any case, as shown by Sikka et al [ 43 , 44 , 51 ], the mDES may also be usefully employed by external judges as a wide checklist of emotional categories to classify emotions in dream reports.…”
Section: Discussionmentioning
confidence: 99%
“…It must be acknowledged here that, according to some authors [ 44 , 63 , 64 ], self-ratings of dream emotions based on emotion rating scales may be biased by demand characteristics of the rating task (i.e., individuals may be primed by answer options) or phenomena such as the positivity offset (i.e., the tendency to experience mildly positive mood most of the time [ 65 ]); still, several authors argue that self-ratings more validly represent dream emotional experiences [ 39 , 66 , 67 ]; see also [ 44 ] for an extensive discussion of pros and cons of self- and external dream emotion ratings). In any case, as shown by Sikka et al [ 43 , 44 , 51 ], the mDES may also be usefully employed by external judges as a wide checklist of emotional categories to classify emotions in dream reports.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individual differences in the positivity offset predicted the spatial learning for positive stimuli, whereas individual differences in the negativity bias predicted the spatial learning for negative stimuli (Norris et al 2011). Early electrical neuroimaging research indicated that the negativity bias is associated with a larger late positive potential (Ito & Cacioppo 2000;Ito et al 1998;Smith et al 2006), and recent work suggests that the positivity offset and negativity bias are associated differently to two serotonin receptor genes (Ashare et al 2013). In sum, although most individuals exhibit both a positivity offset and a negativity bias, this is not true for all individuals, and stable individual differences in the positivity offset and negativity bias exist and predict what is learned about the world.…”
Section: Conclusion: Politics and Controversymentioning
confidence: 99%
“…From an evolutionary perspective, this activation function enables organisms to explore novel environments, with the ultimate goal to find additional sources of nourishment and protection as well as occasions for mating and reproduction (Cacioppo & Berntson, 1994;Cacioppo & Gardner, 1999). Research has shown that positivity offset (as well as negativity bias) can be generalized across different kinds of stimuli (Norris, Larsen, Crawford, & Cacioppo, 2011), is temporally stable and trait-like consistent (Ito & Cacioppo, 2005), and can be used as a theoretical construct to interpret serotonergic function in healthy and clinical populations (Ashare, Norris, Wileyto, Cacioppo, & Strasser, 2013;Carver, Johnson, & Joormann, 2009;Gollan et al, 2016). During our task, positivity offset may have outweighed negativity bias because of the absence of proximal environmental danger which, in turn, promoted exploration (Ito & Cacioppo, 2005;Schettino, Loeys, Bossi, & Pourtois, 2012;Schettino, Loeys, Delplanque, & Pourtois, 2011;Schettino, Loeys, & Pourtois, 2013).…”
Section: Pleasant Information Is Prioritized In Early Visual Cortexmentioning
confidence: 99%